Product Quality and Corporate Financial Performance of Bursa Malaysia - Abbas, Yasir Abdullah; Sabti, Yousif Mousa; Al-Jazaeri, Mohammed Basim Mohammed; Khadher, Hussein Ali Hadi Abu; Taengkliang, Buppachat (South Asian Journal of Social Sciences and Humanities, 2023)
The goal of this paper is to determine the influence of the product quality on the corporate  financial performance (CFP) of Bursa Malaysia (BM) as a developing market. This study  employs secondary data derived from the content analysis of the Datastream and annual reports  of 140 sampled listed on BM for the period of 2008–2018 and utilises the OLS and WLS  regressions. The consequences illustration that there is a positive and important link among product quality with CFP. To the researchers’ best knowledge, this study makes a significant  contribution in terms of product in BM firms.
Keywords: Product quality; corporate financial performance; Bursa Malaysia